STEMATIZAÇÃO DOS DADOS COLETADOS NO PROJETO DE EXTENSÃO ECODESIGN PARA ACATA - Reis, Alessandro M. d.; Straliotto, Luis M.; Grossmann, Fabiane V.; Santos, Alessandro Z. d. (Salão do Conhecimento, 2013)
Resumo